2001
DOI: 10.1103/physrevlett.86.4938
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cloning of Coherent States with a Linear Amplifier and Beam Splitters

Abstract: A transformation achieving the optimal symmetric N → M cloning of coherent states is presented. Its implementation only requires a phase-insensitive linear amplifier and a network of beam splitters. An experimental demonstration of this continuous-variable cloner should therefore be in the scope of current technology. The link between optimal quantum cloning and optimal amplification of quantum states is also pointed out.PACS numbers: 03.65.Bz, 42.50.Dv, 89.70.+c Quantum systems cannot be cloned exactly [1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
153
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 25 publications
(40 reference statements)
1
153
0
Order By: Relevance
“…Optimal Gaussian cloning can be realized using a phase insensitive amplifier and a beam splitter [10,11]. However, it has been recently shown, theoretically and experimentally, that the parametric amplifier can be replaced by a simpler scheme involving only linear optical components, homodyne detection and a feed-forward loop [12].…”
Section: The Linear Cloning Machinementioning
confidence: 99%
See 2 more Smart Citations
“…Optimal Gaussian cloning can be realized using a phase insensitive amplifier and a beam splitter [10,11]. However, it has been recently shown, theoretically and experimentally, that the parametric amplifier can be replaced by a simpler scheme involving only linear optical components, homodyne detection and a feed-forward loop [12].…”
Section: The Linear Cloning Machinementioning
confidence: 99%
“…Note that in this Section we are addressing the case of an unknown squeezing parameter ξ (randomly distributed according to a given probability density): when it is known, the optimal strategy in the Gaussian regime is to perform the unsqueezing operation S −1 (ξ) just before the cloning machine, proceed as in the case of coherent states, and, at the output stage, apply the squeezing operation S(ξ) to both the clones which yields a fidelity of 2/3 (independent on the amount of fixed squeezing) as in the coherent state case [10]. However in the case of an unknown squeezing parameter the squeezing action S(ξ) is not known.…”
Section: Squeezed Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…While Gaussian states, defined as states with a Gaussian Wigner function, are known to provide useful resources for tasks such as teleportation [2,3], cloning [4][5][6], or dense coding [7][8][9], there is an ongoing effort to study which protocols are allowed by non-Gaussian resources. The most notable example is certainly their use for an optical quantum computer [10,11], alongside their employment for improving teleportation [12][13][14], cloning [15], and storage [16].…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…We also derive the best transformation efficiencies. [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22] which operate either in a deterministic or probabilistic way. Corresponding to the quantum no-cloning theorem, Pati and Braunstein [23] demonstrated that the linearity of quantum mechanics also forbids one to delete one unknown state ideally against a copy [23], which is called the quantum no-deleting principle.…”
Section: Introductionmentioning
confidence: 99%